Proteomic analysis of Aspergillus fumigatus – clinical implications. (2nd July 2016) - Moloney, Nicola M.; Owens, Rebecca A.; Doyle, Sean
ABSTRACT: Introduction : Aspergillus fumigatus is a ubiquitous saprophytic fungus capable of producing small airborne spores, which are frequently inhaled by humans. In healthy individuals, the fungus is rapidly cleared by innate mechanisms, including immune cells. However, in individuals with impaired lung function or immunosuppression the spores can germinate and prompt severe allergic responses, and disease with limited or extensive invasiveness. Areas covered : The traits that make A. fumigatus a successful colonizer and pathogen of humans are multi-factorial. Thus, a global investigative approach is required to elucidate the mechanisms utilized by the fungus to cause disease. Expert commentary : In doing so, a better understanding of disease pathology can be achieved with improved therapeutic/diagnostic solutions, thereby improving patient outcome. Proteomic analysis permits such investigations and recent work has yielded insight into these mechanisms.